2009
DOI: 10.1038/labinvest.2009.69
|View full text |Cite
|
Sign up to set email alerts
|

The role of epithelial malfunction in the pathogenesis of enteropathogenic E. coli-induced diarrhea

Abstract: The homeostatic balance of the gastrointestinal tract relies on a single layer of epithelial cells, which assumes both digestive and protective functions. Enteric pathogens, including enteropathogenic Escherichia coli (EPEC), have evolved numerous mechanisms to disrupt basic intestinal epithelial functions, promoting the development of gastrointestinal disorders. Despite its non-invasive nature, EPEC inflicts severe damage to the intestinal mucosa, including the dysregulation of water and solute transport and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…It is of interest now to determine whether a similar pattern is found in the in vivo setting, by employing a relevant animal model of human disease. EPEC, which is related evolutionarily to EHEC O157 : H7, does not contain Shiga toxins but does possess the LEE pathogenicity island and produces attaching and effacing lesions on eukaryotic cells in tissue culture exposed to the human enteric pathogen (Lapointe et al, 2009). With respect to NF-kB signalling, previous studies have reported that EPEC inhibits IKK, MAPK and P-I3 kinase signal transduction pathways in a T3SS-dependent manner (Ruchaud-Sparagano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest now to determine whether a similar pattern is found in the in vivo setting, by employing a relevant animal model of human disease. EPEC, which is related evolutionarily to EHEC O157 : H7, does not contain Shiga toxins but does possess the LEE pathogenicity island and produces attaching and effacing lesions on eukaryotic cells in tissue culture exposed to the human enteric pathogen (Lapointe et al, 2009). With respect to NF-kB signalling, previous studies have reported that EPEC inhibits IKK, MAPK and P-I3 kinase signal transduction pathways in a T3SS-dependent manner (Ruchaud-Sparagano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pathogens can alter barrier function by altering MLC phosphorylation. For example, both EPEC and H. pylori can activate MLCK, causing actomyosin ring contraction, disruption of TJ proteins, and increased permeability (36, 69,110,149,163). The regulation of Rho GTPases is tightly monitored in the cell, and either activation or inhibition of its ROCK phosphorylating capabilities can result in aberrant barrier function.…”
Section: Mechanisms Of Probiotic Functionmentioning
confidence: 99%
“…These bacteria have evolved a number of strategies that allow them to directly augment, disrupt, or inhibit epithelial cell function including invasion of epithelial cells, molecular mimicry, activation of intracellular signaling pathways, formation of pores, and alteration of cytoskeleton-dependent functions. [33][34][35][36] There is a general consensus that A/E pathogens increase epithelial permeability 37 and induce changes in epithelial secretion and absorption that result in diarrhea. This topic was the focus of several recent excellent reviews.…”
Section: Stats and Adaptive Immunity (Fig 2)mentioning
confidence: 99%
“…This topic was the focus of several recent excellent reviews. 37,38 Although co-option of epithelial cell function to promote colonization is the initial action of A/E pathogens, the resulting upregulation of Th1 cytokines is important in sustaining initial bacterial effects on permeability. Of interest is that loss of absorptive surface is a consequence of infection, but the effects on epithelial permeability do not appear to be due to epithelial apoptosis.…”
Section: Stats and Adaptive Immunity (Fig 2)mentioning
confidence: 99%